Foreign Office and Foreign and Commonwealth Office: Embassy and Consulates, Union of Soviet Socialist Republics (formerly Russian Empire): General Correspondence (Records of the Public Record Office., 1981)
This series contains general correspondence of the British embassy and consulates in the Union of Soviet Socialist Republics (formerly the Russian Empire). There is no correspondence for the period 1921 to 1937.